Use of traditional cooking fuels and risk of young adult cataract in rural Bangladesh : a hospital-based case-control study - Joydhan Tanchangya (Prince of Songkla University, 2021)
Thesis (M.S., Epidemiology)--Prince of Songkla University, 2010